Adolescents’ lived experience of panic disorder: an interpretative phenomenological analysis - Baker, HJ; Hollywood, A; Waite, P (BioMed Central, 2022)
Background Panic disorder is a debilitating anxiety disorder that has a serious impact on adolescents’ social and academic functioning and general wellbeing. Panic disorder is experienced by around 1 to 3% of the adolescent population. The aim of this study was to examine adolescents’ experiences of having panic disorder.